2018
DOI: 10.1103/physreve.97.042307
|View full text |Cite
|
Sign up to set email alerts
|

Multiple scales in metapopulations of public goods producers

Abstract: Multiple scales in metapopulations can give rise to paradoxical behavior: in a conceptual model for a public goods game, the species associated with a fitness cost due to the public good production can be stabilized in the well-mixed limit due to the mere existence of these scales. The scales in this model involve a length scale corresponding to separate patches, coupled by mobility, and separate time scales for reproduction and interaction with a local environment. Contrary to the well-mixed high mobility lim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 77 publications
0
23
0
Order By: Relevance
“…It will also be critical to evaluate the extent to which spatial interactions modify strategy-environment feedback in proposed generalizations [15] of the replicator framework underlying the present work [4] and in stochastic games with feedback between behavior and public good states [16]. Finally, the spatial approach may also aid efforts to understand how microorganisms produce and utilize public goods, e.g., siderophores -extracellular iron harvesting enzymes [6,[17][18][19][20]. Given increasing pressures on limited resources, we intend to leverage prior work on controlling mean-field strategy-environment dynamics [21] to identify ways in which local manipulation of resources, strategies, and/or perceptions can help stabilize and conserve the commons.…”
mentioning
confidence: 99%
“…It will also be critical to evaluate the extent to which spatial interactions modify strategy-environment feedback in proposed generalizations [15] of the replicator framework underlying the present work [4] and in stochastic games with feedback between behavior and public good states [16]. Finally, the spatial approach may also aid efforts to understand how microorganisms produce and utilize public goods, e.g., siderophores -extracellular iron harvesting enzymes [6,[17][18][19][20]. Given increasing pressures on limited resources, we intend to leverage prior work on controlling mean-field strategy-environment dynamics [21] to identify ways in which local manipulation of resources, strategies, and/or perceptions can help stabilize and conserve the commons.…”
mentioning
confidence: 99%
“…The public goods game has been extensively used in the context of human societies, and the concepts have been applied to other systems, such as microbial colonies, and insect communities (Hofbauer & Sigmund 1998, Hauert et al 2006, Nowak 2006, Allen et al 2013, Nanda & Durrett 2017, Bauer & Frey 2018. In this model, both the producer and non-producer benefit from the products produced solely by the former (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Phenotypic delay may also affect other processes. For example, it was recently shown that a delay in evolutionary adaptation can lead to coexistence of spatial populations, in cases where immediate adaptation would eradicate coexistence [91,92]. A delay in evolutionary adaptation has also been postulated to explain the effect of antibiotic pulses of different lengths on the probability of resistance emerging [93].…”
Section: Discussionmentioning
confidence: 99%